Innovation of a paper bag for LetsVACATION.COM using the implementation of augmented reality technology / Abdul Muiz Abdul Fatah ... [et al.] - Abdul Fatah, Abdul Muiz; Omar, Mastura; Mohd Rosnan, Shalida; Zakaria, Siti Farhana; Abdul Azim, Intan Natasha (Universiti Teknologi MARA, Kedah, 2023)
LetsVACATION.COM by Hararei Travel and Tours Sdn Bhd was set up on July 2022, located at Bandar Baru Lembah Selatan, Southville, Selangor. Travel agencies offer simple vacations, tickets, hotel/accommodation reservations, all-inclusive packages, corporate meetings, conferences, and incentive travel programs. Typically, travel agencies would give their clients pamphlets, flyers, paperwork, and occasionally gifts and items to say thanks. But LetsVACATION.com does not yet have a bag of any type in which to store the items they give their customers. I, therefore, intend to design the business's paper bag. The goal of the paper bag development is to provide good packaging that aids in the marketing of the agency with a new paper bag that contains information, to assist LetsVACATION.COM in improving client convenience and to outperform competitors in terms of rates. Paper bags are still widely used today since they are convenient for carrying and can accommodate a variety of products. Paper bags are being used by businesses for events, branding, seminars, and promotion. Since they want clients to be aware of their business and the products they provide, this firm wants to have a paper bag. They wish to have a paper bag with the firm name, logo, address, and AR to increase brand awareness. AR Technology has many advantages as it can be used to store information in the form of a virtual display. It also can be scanned from many angles as long as it is within the frame of the device being used.